Effects of Health on Wages of Australian Men - Cai, L (My University, 2007)
As a form of human capital health like education determines individuals’ productivity and thus wage rates. While there are numerous overseas studies that examine the effect of health on wages, research on this issue using Australian data is scarce. This paper uses the Household, Income and Labour Dynamics in Australia (HILDA) survey to investigate the effect of health on the wages of working-age Australian men. A simultaneous equation model of health and wages is estimated to account for endogeneity of health. The results confirm the finding in the literature that health has a significant and positive effect on wages, but the significant effect is found only when measurement error and endogeneity of health are accounted for. The reverse effect of wages on health is found insignificant, but there is evidence on the endogeneity of health arising from unobserved factors.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Melbourne Institute Working Papers
Keywords: Employment -- Labour force participation; Employment; Health; Labour market; Employment and unemployment